Seleksi In Vitro dan Pengujian Mutan Tanaman Pisang Ambon Kuning untuk Ketahanan terhadap Penyakit Layu Fusarium - Deden Sukmadjaja; Ragapadmi Purnamaningsih; Tri P. Priyatno (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2013)
Fusarium wilt of banana (Musa spp.) caused byFusarium oxysporum f. sp. cubense (Foc) is the most seriousproblem faced in banana cultivation in terms of plantproductivity and fruit quality. Mutation breeding is one of thealternative method that can be applied in producing newbanana cultivar. Mutants can be induced by chemicalmutagen such as ethyl methane sulfonate (EMS) followed byin vitro selection and then evaluation of the mutants tofusarium wilt disease in glasshouse and Foc infected field.The aim of this research was obtained EMS induced and invitro selected mutants of banana var. Ambon Kuning andevaluated Foc disease resistant clones in glasshouse andFoc infected field. The first step to obtain the explants forthis research was initiation and formation of multiple budclumps (MBC) using MS basal media supplemented with 5,10, and 20 mg/l of benzyladenin. Plant regeneration of MBCwas also studied by using MS media containing 0, 0.2, and 1mg/l of benzyladenin. To induce mutagenesis, MBC wassoaked in 0.1, 0.3, and 0.5% (v/v) EMS for 1, 2, and 3 hours.The assesment of resistant MBC mutants to Fusariumphytotoxin was conducted by using fusaric acid (FA) asselection agent in concentration of 30, 45, and 60 ppm.Putative mutant plants produced by in vitro selection werefurther tested using spore solution of Foc race 4 inglasshouse. Meanwhile, Foc resistance assesment in theinfected field was conducted in Pasirkuda ExperimentalStation, Bogor Agricultural University. The results showedthat MBC can be formed in MS basal media supplementedwith 10 or 20 mg/l benzyladenin. The EMS played a role inobtaining mutants by producing 68 MBC putative mutantstolerant to Foc based on FA selection. Further evaluation inthe glasshouse was obtained 64 Foc resistant plants from391 putative mutants produced by in vitro selection.Evaluation in the Foc infected field showed six clonessurvived until generative phase (12 month of age).